Wine, Brains, and Snakes: An Ancient Roman Cult between Gendered Contaminants, Sexuality, and Pollution Beliefs. (19th April 2018) - Ambasciano, Leonardo
Abstract : The present contribution, concerning the ancient Roman cult of Bona Dea, explores the interplay between intuitive healing beliefs, morality, disgust, and coercive control of sexual behaviours. In order to preliminarily investigate cultural variations concerning sex and gender issues in past societies (a somewhat neglected topic in current cognitive studies), this article engages the socio-sexual organization of Roman culture which underpinned the cult devotion, explaining the evolutionary rationale of the underlying mythography as a mate-guarding strategy and the cult itself as a relief valve and a temporary compensation for subordinate women. The essential components of the cult (i.e., wine and snakes) are further analysed via evolutionary psychology and the cognitive science of religion. The final paragraph tackles the problematic scholarly reconstruction of the cult's promise of an afterlife for its worshippers, arguing that a phylogenetic analysis of Graeco-Roman mythographies might help contextualizing this issue.